Research on the gamma irradiation decomposition products of 2, 6-diamino-3, 5-dinitropyrazine-1-oxide (LLM-105). (October 2022) - Xiao, Qian; Sui, Heliang; Yin, Ying; Liao, Longyu; Wang, Huaihua; Fu, Xiaolin; Wang, Jingkai; Ai, Jin; Ju, Xin
Abstract: In this work, 60 Co gamma-ray source was used to irradiate LLM-105 at room temperature with the radiation doses of 100, 300, 500, 696, and 900 kGy under vacuum. High-performance liquid chromatography coupled with electrospray mass spectrometry (HPLC–MS) and 1 H nuclear magnetic resonance (NMR) demonstrated the main radiolysis product in gamma-irradiated LLM-105 was 2, 6-diamino-3, 5-dinitropyrazine (ANPZ). The relationship between ANPZ content and irradiation dose indicated that LLM-105 was a stable explosive under gamma irradiation. The sensitivity is not expected to change based on the chemical analyses performed on irradiated LLM-105. The radiation decomposition mechanism of LLM-105 was clarified by Atomic dipole moment corrected Hirshfeld (ADCH) atomic charges and electronic localization function (ELF). Highlights: 2, 6-diamino-3, 5-dinitropyrazine-1-oxide is an insensitive explosive to irradiation. 2, 6-diamino-3, 5-dinitropyrazine is the main radiolysis product. Clarified the relationship between radiolysis product content and irradiation dose. Acyl O is easier to accumulate the energy of gamma rays.